Boletim Atlas ODS Amazonas V.2 N.8 - Especial COVID-19 - Pereira, Henrique dos Santos (Brasil, 2020)
In this 8th Special Report, the effectiveness of the measures adopted by the municipalities of Amazonas since the beginning of the pandemic of COVID-19 was evaluated. The reaction time of the municipal public administration and the types of measures adopted were evaluated in terms of the number of cases of the disease registered until May 21. The results indicate that the most effective governments were the ones that adopted the most stringent measures early.